GROSS PATHOLOGY AND HISTOPATHOLOGY DESCRIPTION OF NERVOUS SYSTEM OF BALI DUCK AFTER EXPERIMENTAL INFECTION WITH AVIAN ORTHOAVULAVIRUS 1 TABANAN-1/ARP/2017 ISOLATE - Sari, Yeni Ratna; Adi, Anak Agung Ayu Mirah; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2022)
The present study aims to determine the gross pathology and histopathological changes in the organs of the cerebrum, cerebellum, spinal cord, and sciatic nerve in bali ducks infected with Avian orthoavulavirus type 1 Tabanan-1/ARP/2017 isolate. The present study used 15 male bali ducks aged 21 days which had been acclimatized for two weeks. Ten ducks were treated for infection (P 1 ) were infected with AOAV-1 Tabanan-1/ARP/2017 isolate at a dose of 0.5 ml/27 HAU intraocularly, and 5 control ducks (P 0 ) were given Phosphate Buffered Saline solution as much as 0.5 ml intraocularly. Then the dead ducks were necropsied for gross pathology examination. The nervous organs were processed and stained for hematoxylin-Eosin, then performed histopathological examination. Gross pathological change was found encephalomalacia in the cerebrum and cerebellum. Histopathological changes were dominated by congestion, perivascular edema, endothelial proliferation, neuropil vacuolization, vasculitis , and gliosis of central nervous system organs. Meanwhile, the histopathological appearance of sciatic nerve is congestion.